(untitled) - Adds, Brian (London, UK, 1982)
Studying Strategies is the fourth book in the Strategies series. The book contains 15 units of k\work, arranged in groups of four teaching units followed by a consolidation unit. Each unit is based on internationally relevant themes - foreign travel, crime, medicine and health, festivals, science and technology. The sources is designed for intermediate students aged 16 or over.
Keywords: English language,Ngôn ngữ tiếng Anh